2012
DOI: 10.1371/journal.pone.0034078
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Apolipoprotein Levels Are Associated with Cognitive Status and Decline in a Community Cohort of Older Individuals

Abstract: ObjectivesApolipoproteins have recently been implicated in the etiology of Alzheimer’s disease (AD). In particular, Apolipoprotein J (ApoJ or clusterin) has been proposed as a biomarker of the disease at the pre-dementia stage. We examined a group of apolipoproteins, including ApoA1, ApoA2, ApoB, ApoC3, ApoE, ApoH and ApoJ, in the plasma of a longitudinal community based cohort.Methods664 subjects (257 with Mild Cognitive Impairment [MCI] and 407 with normal cognition), mean age 78 years, from the Sydney Memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
149
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(160 citation statements)
references
References 74 publications
7
149
4
Order By: Relevance
“…There was no significant difference in background variables in any of the samples between the two different KIBRA genotype groups (see Table 1), or between the four different KIBRA/CLSTN2 genotype groups (data not shown). APOE genotyping was performed using Taqman genotyping assays for the two SNPs, rs429358 and rs7412 to genotype the three APOE alleles, ε2/3/4 as per Song et al 2012. Participants were classified as an APOE ε4 carrier or not.…”
Section: Genotypingmentioning
confidence: 99%
“…There was no significant difference in background variables in any of the samples between the two different KIBRA genotype groups (see Table 1), or between the four different KIBRA/CLSTN2 genotype groups (data not shown). APOE genotyping was performed using Taqman genotyping assays for the two SNPs, rs429358 and rs7412 to genotype the three APOE alleles, ε2/3/4 as per Song et al 2012. Participants were classified as an APOE ε4 carrier or not.…”
Section: Genotypingmentioning
confidence: 99%
“…This increase in HDL prevents cholesterol depositing in blood vessels (Segrest, 2013;Haram et al, 2009;Jenkins et al, 2010 andMichelle, 2009). Increasing HDL increases the level of Apo A as its major component (Ghorbanian et al, 2013;Song et al, 2012). Moreover, studies approve of the positive effects of physical activities and believe that physical activities significantly increase Apoprotein A and decrease Apoprotein B levels (Arazi, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Lipoproteins are formed by particles called lipids and proteins including free cholesterol, esterified cholesterol, triglyceride and phospholipids along with quadruple lipids (Song et al, 2012). The proteins of lipoprotein structure are called Apo lipoprotein and Apo protein (Niklas et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…APOA1 is also one of the main apolipoproteins, together with apolipoprotein E (ApoE), identified in cerebrospinal fluid (CSF) (13). A recent community-based cohort study of elderly M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 3473 4 individuals found a lower concentration of APOA1 in subjects with MCI, compared with cognitively normal (CN) subjects, and observed that both a low baseline plasma APOA1 level and a high plasma apolipoprotein B (APOB)/APOA1 ratio are powerful predictors of cognitive decline in CN subjects (i.e., the progression from a Clinical Dementia Rating [CDR] score of 0 at baseline to a CDR score > 0 after 2 years) (14).…”
Section: Pib-negative Amci [Amci-]) Is Likely Related To Other Pathopmentioning
confidence: 99%